Civic engagement in the perspective of citizenship towards civil society - Buldani, Asep Anggi; Dewi, Dinie Anggraeni; Sutanto, Zulkifli Alamsah; Bety, Cici Fitri; Utami, Nissa Aulia Belistiana (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2026)
Civic engagement—encompassing social awareness, volunteerism, political participation, activism, and communal solidarity—is an indispensable pillar of modern nationhood. Such proactive involvement is non-negotiable for the preservation of democratic institutions and the construction of an equitable, robust civil society. Employing a rigorous literature review methodology, this study critically analyses peer-reviewed journals, academic monographs, and institutional documents to synthesise existing theoretical frameworks and empirical evidence. This approach forcefully addresses prevailing methodological gaps to establish a solid conceptual foundation for subsequent analysis. Citizen engagement, whether manifested through grassroots activism or formal political avenues, explicitly frames specific socio-political issues within the juridical parameters of citizenship—specifically, the reciprocal rights and obligations binding the individual to the state. Furthermore, the collective mobilisation of communities demonstrates a clear capacity to shape public policy and secure equitable jurisprudential outcomes. Ultimately, this study asserts a comprehensive paradigm of civic engagement within the citizenship continuum, unequivocally elucidating the critical mechanisms required to achieve absolute participatory parity.